Preliminary Evaluation of the Use of Thermally-Dried Immobilized Kefir Cells in Low Alcohol Winemaking - Anastasios Nikolaou; Georgios Sgouros; Valentini Santarmaki; Gregoria Mitropoulou; Yiannis Kourkoutas (Applied Sciences, 2022)
Low alcohol wines (≤10.5% vol) are novel products that have gradually been gaining the consumers’ and market’s interest over the last decade. Taking into account the technological properties of immobilized cell systems alongside with the commercial need for dry cultures, the aim of the present study was to assess the suitability of thermally-dried immobilized kefir cells on DCM, apples pieces, and grape skins in low alcohol wine production. Storage of thermally-dried kefir culture in various temperatures (−18, 5, and 20 °C) resulted in high viability rates for immobilized cells (up to 93% for yeasts/molds immobilized on grape skins and stored at −18 °C for 6 months). Fermentation activity was maintained after storage in all cases, while high operational stability was confirmed in repeated batch fermentations for a period of 6 months. Principal Component Analysis (PCA) revealed that the fermentation temperature rather than the state of kefir culture affected significantly volatiles detected by Head Space Solid-Phase Microextraction Gas Chromatography–Mass Spectrometry analysis. Notably, all new products were of high quality and approved by the sensory panel.